1988
DOI: 10.1016/0014-5793(88)81448-0
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of a calcium‐phospholipid‐dependent protein kinase in the maturation of Xenopus laevis oocytes

Abstract: It has been described that phosphorylation, and dephosphorylation, of specific proteins is associated with key events of the cell cycle and is likely to be due to activation of kinase(s). From our results, the presence of calcium-phospholipid-dependent protein kinase (PKC) was clearly demonstrated in both the cytosolic and particulate fractions of immature Xenopus laevis oocytes and in the cytosolic fraction of mature oocytes. However, it was less active in metaphase II-than in prophase I-arrested oocytes. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Treatment of Xenopus oocytes with PMA has been reported to induce meiotic maturation in the absence of progesterone (Stith & Mailer, 1987;Laurent et al, 1988). In fact, in several aspects the PMA-induced changes in the properties of the oocyte plasma membrane observed here resemble those occurring during progesterone-induced maturation.…”
Section: Correlations To Meiotic Maturationmentioning
confidence: 52%
See 2 more Smart Citations
“…Treatment of Xenopus oocytes with PMA has been reported to induce meiotic maturation in the absence of progesterone (Stith & Mailer, 1987;Laurent et al, 1988). In fact, in several aspects the PMA-induced changes in the properties of the oocyte plasma membrane observed here resemble those occurring during progesterone-induced maturation.…”
Section: Correlations To Meiotic Maturationmentioning
confidence: 52%
“…Activation of protein kinase C has been reported to be involved in stimulation of meiotic maturation (Laurent et al, 1988 and Methods). Under control conditions, the average capacitance is 179 -+ 5 nF.…”
Section: Capacitancementioning
confidence: 98%
See 1 more Smart Citation
“…We therefore examined the role of PKC during cavitation. Protein kinase C can be activated by phorbol esters or synthetic diacylglycerols [32][33][34][35][36][37]. To establish that the phorbol ester PMA and the synthetic diacylglycerol OAG up-regulate PKC, we monitored the ability of these agents to induce compaction of early 8-cell embryos [37,38].…”
Section: Resultsmentioning
confidence: 99%
“…Weak support for a link between DAG levels and PKC activity was found by Laurent et al (1988), who reported that PKC activity is low in eggs obtained an unknown number of hours after white spot appearance (although MPF activity was higher in eggs). This agrees with the decline in DAG levels after 0.85 GVBD,,.…”
Section: Comparison Of the Action Of Three Hormonesmentioning
confidence: 90%